Potential benefits and harms of NADPH oxidase type 4 in the kidneys and cardiovascular system. Issue 4 (21st June 2018) - Rajaram, Renuga D; Dissard, Romain; Jaquet, Vincent; de Seigneux, Sophie
Abstract: The main function of NADPH oxidases is to catalyse the formation of reactive oxygen species (ROS). NADPH oxidase 4 (NOX4) is expressed at high levels in kidney tubular cells, and at lower levels in endothelial cells, cardiomyocytes and other cell types under physiological conditions. NOX4 is constitutively active producing hydrogen peroxide (H2 O2 ) as the prevalent ROS detected, whereas other NOX isoforms present in the renal and cardiovascular systems (i.e. NOX1, NOX2 and NOX5) generate superoxide radical anions as main products. Pharmacological inhibition of NOX4 has received enormous attention for its potential therapeutic benefit in fibrotic disease and nephropathologies. Ongoing clinical trials are testing this approach in humans. Diabetes elevates NOX4 expression in podocytes and mesangial cells, which was shown to damage glomeruli leading to podocyte loss, mesangial cell hypertrophy and matrix accumulation. Consequently, NOX4 represents an interesting therapeutic target in diabetic nephropathy. On the contrary, experiments using NOX4-deficient mice have shown that NOX4 is cytoprotective in tubular cells, cardiomyocytes, endothelial cells and vascular smooth muscle cells, and has a metabolism-regulating role when these cells are subjected to injury. Mice with systemic NOX4 deletion are more susceptible to acute and chronic tubular injury, heart failure and atherosclerosis. Overall, the current literature suggests a detrimental role of increased NOX4 expression in mesangial cells and podocytes during diabetic nephropathy, but a cytoprotective role of this enzyme in other cellular types where it is expressed endogenously. We review here the recent evidence on the role of NOX4 in the kidneys and cardiovascular system. With the emergence of pharmacological NOX4 inhibitors in clinical trials, caution should be taken in identifying potential side effects in patients prone to acute kidney injury and cardiovascular disease.